SISTEM INFORMASI GEOGRAFIS PEMETAAN BANYAKNYA KEJADIAN BENCANA ALAM DI PROVINSI JAWA BARAT BERBASIS WEB - Rizqa Zahrotun Nafiah; Bambang Agus Herlambang; Ahmad Khoirul Anam (CV. ADIBA AISHA AMIRA, 2024)
West Java Province is one of the areas in Indonesia that is often affected by natural disasters, such as floods, landslides, and earthquakes. According to the West Java BPBD, in 2023 there were 970 disaster events in West Java Province, which resulted in 26 deaths and 98,860 people displaced. As a disaster-prone area, information about disasters is needed by the community to monitor disasters that occur. This research aims to develop a Geographic Information System (GIS) mapping the number of natural disasters in West Java Province used to store and display disaster distribution maps. This GIS was developed using HTML, CSS, and Javascript programming languages. The results of this research are in the form of a geographic information system mapping the number of natural disaster events in West Java Province where users can view data in tabulation and graphics.